1980
DOI: 10.1002/1097-0142(19800815)46:4<706::aid-cncr2820460412>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical diagnosis of prostatic cancer with metastasis

Abstract: An immunohistochemical method for detecting prostatic acid phosphatase is described for the diagnosis of metastatic prostatic carcinoma. The specific antiserum against prostatic acid phosphatase was prepared from rabbit by injection of acid phosphatase purified from seminal fluid. This method gives a selective staining of the cytoplasm of the glandular epithelial cells of prostatic tissue specimens on paraffin section. Most of the non-prostatic tissues were negative except for occasional weak staining in granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…With the PASE/4LJ monoclonal antibody no staining was seen in granulocytes (Yam et al, 1981), osteoclasts (Jobsis et al, 1981), parietal cells of the stomach, liver cells, renal cell or breast carcinomas (Li et al, 1980;Yam et al, 1981).…”
Section: Discussionmentioning
confidence: 96%
“…With the PASE/4LJ monoclonal antibody no staining was seen in granulocytes (Yam et al, 1981), osteoclasts (Jobsis et al, 1981), parietal cells of the stomach, liver cells, renal cell or breast carcinomas (Li et al, 1980;Yam et al, 1981).…”
Section: Discussionmentioning
confidence: 96%
“…The studies have generally confirmed that the preponderance of PAP expression is in the prostate, though several studies have noted some extra-prostatic expression. PAP expression has been reported in liver cells, normal adult kidney [11,15]; granulocytes, parietal cells of the stomach [15]; urethral glands [16,17]; anal gland non-mucosal epithelium, rectal tissue [16]; salivary glands [18]; and ectopic prostate tissue in both uterine cervix and vagina [19].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, several studies failed to observe PAP staining in normal tissues, including bladder, breast, colon/rectum, epidermis, kidney, liver, lung, ovary, salivary glands, stomach, testes, and urethra [11,12,15,16]. Using qPCR to measure relative levels of PAP mRNA transcripts, Cunha and colleagues [14] found that, relative to prostate, PAP mRNA was expressed at low levels in several normal tissues, most notably in placenta, kidney, and testis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations